Promoção da caminhada no lazer e alimentação saudável na atenção pré-natal: estudo de intervenção controlado - Malta, Maíra Barreto [UNESP] (2015)
Objective: to design, implement and evaluate the effectiveness of an intervention - systematic insertion of promoting healthy eating and leisure-time walking during in routine prenatal care performed by doctors and nurses in family health care units - over five dietary practices and the realization of leisure-time walking at by pregnant women. Methods: this is a controlled intervention study, not randomized, in which took part 42 doctors/nurses and a sample (n=353) of pregnant women attended by those professionals in primary health care settings to public health care in the city of Botucatu-SP, Brazil. The study has been divided into two stages. The first one was the implementation and evaluation of an educational activity (EA), with 16 hours, by attendance, addressed to doctors and nurses who assist pregnant women in nine family health care units, in order to extend/adapt their knowledge of nutrition and physical activity during pregnancy and then introduce routinely and systematically in prenatal care the promotion of 5 dietary practices (3 fruit daily; 2 servings of vegetables and two servings of beans, at least 5 days a week; sporadic consumption (maximum once a week) of soda and / or industrialized cookie), and guidance of pregnant women to walking during leisure time. The knowledge and practices of the participants (n=22) before and after the EA, have been compared to a control group (n=20), formed by professionals of eight traditional health care units not involved in the educational activity. This knowledge has been evaluated in both groups with a self-applied questionnaire, elaborated for this research; practices (guidance for leisure-time walking and healthy eating) have been measured by interviews with pregnant women assisted by two professional groups, in their homes. We have generated two scores of knowledge (about walking and nutrition) and we have used ANOVA for repeated measures to assess changes before and after the ...